PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PADA PT. HASJRAT ABADI DAN BENGKEL-BENGKEL TOYOTA DI MANADO - Umboh, Arjunal; Tumbel, Tinneke; Rogahang, Joula (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
Workshop in the city of Manado exposed to levels of increasingly fierce competition, therefore the company needs to improve performance in order to survive in a crisis situation or win the competition in the era of globalization Order to determine the effect of working capital management (efficiency of cash, accounts receivable, and inventory). To determine the effect on the profitability of cash efficiency garage PT. Eternal Hasjrat  KC Manado and Workshop - Workshop in Manado.  This type of research is based on the clarity of the elements, research steps are already planned until cooked when preparations are prepared, the use of the sample and the findings apply to the population, the presence of the hypothesis, the expected results, data collection, and data analysis performed after all the data collected, this study categorized into quantitative research Results: Efficiency cash positive effect of 0.002 with 0.505 significance level is much greater than the significance level of 0.05.  This result explains that the cash efficiency does not significantly affect the profitability of the Workshop PT. Hasjrat Abadi and Workshop - Toyota workshop in Manado. This means that in conditions of efficiency of receivables and inventories remained, changes in the efficiency of cash of any kind will not affect profitability. Efficiency receivables positive effect of 0.005 with 0.159 significance level is much greater than the significance level of 0.05. This result explains that the efficiency of the receivables does not significantly affect profitability at PT. Hasjrat Eternal Repair - Toyota repair shop in Manado. This means that in conditions of efficiency remain cash and inventory, receivables efficiency of any changes will not affect profitability. Efficiency supplies negative effect of -0.003 with a significance level of 0.002 is much smaller than the significance level of 0.05. This result explains that the efficiency of inventory significantly negative effect on profitability at PT. Eternal Hasjrat Manado Workshop - Toyota repair shop in Manado.KEYWORDS  :  Working Capital, Cash Efficiency (X1), Efficiency Receivables (X2), Efficiency Stocks (X3), profitability (Y).